Legal Review Of Malpractice Notary In The Notary’s Deed - Enriko Silalahi; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Article 84 and Article 85 of Law No. 2 year 2014 on the amendments to the Act No. 30 year 2004 concerning Notary Public Official, when a Notary in performs his official duties and is proven to have committed a violation, the Notary may be subjected or sanctioned. The sanction is in the form of civil sanction, administration, and code of ethics of Notary. Besides, if a Notary commits a criminal offense, a criminal sanction may be imposed to him.The purpose of the research was to find out the malpractice of the Notary in the Notary deed, and to find out the role of the Regional Supervisory Board (MPD) in supervising Notaries who carry out malpractice actions.This study used a juridical-normative approach derived from the collection of primary data and secondary data, then they were analyzed by qualitative analysis methods. Data collection techniques used was library studies with qualitative data analysis.The result of the research showed that UUJN does not mention the existence of sanction punishment but a legal action against the violation done by Notary. It invites elements of forgery over intent/negligence in making authentic letter/deed which contains false facts. After administrative sanction/professional code of ethics Notary and civil sanctions, as well as qualified are as a criminal act committed by a Notary. If the notary is proven to have been involved in intentionally committing a crime of forgery of an authentic deed the sanction will be given to him/her.Suggestion to lawmakers to anticipate the different interpretations of the law can be done quickly, so that malpractice Notary will never occur again.Keywords: Sanctions; Notary; Malpractice; Accountability